2003
DOI: 10.1159/000070156
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Quantitation of Urinary Glycosaminoglycans

Abstract: Background: Substantial amounts of glycosaminoglycans (GAGs) are present in the urine of healthy individuals, but the concentration in the serum is very low. This finding suggests that urinary GAGs come from the glomerulus and may reflect the turnover of GAGs in the glomerulus. Hypothesis: However, little is known about the physiologic regulation of the urinary GAGs in humans, and so investigations are needed to evaluate the effects of age and sex on urinary GAGs in normal individuals. Methods: Eighty-seven he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
(33 reference statements)
1
13
0
1
Order By: Relevance
“…They are released into the extracellular environment without passing the lysosomes and end up in urine having the same sugar structure as in vivo. The largest proportion of urinary GAG is chondroitin sulfate (62%-77%), whereas heparan sulfate accounts for ϳ25% and dermatan sulfate for only ϳ5% (214 ). The mucopolysaccharidoses, a group of inborn errors in GAG catabolism, can be diagnosed by measuring increased urinary GAGs.…”
Section: Screening Methods For Unraveling Defects In O-glycosylation mentioning
confidence: 99%
“…They are released into the extracellular environment without passing the lysosomes and end up in urine having the same sugar structure as in vivo. The largest proportion of urinary GAG is chondroitin sulfate (62%-77%), whereas heparan sulfate accounts for ϳ25% and dermatan sulfate for only ϳ5% (214 ). The mucopolysaccharidoses, a group of inborn errors in GAG catabolism, can be diagnosed by measuring increased urinary GAGs.…”
Section: Screening Methods For Unraveling Defects In O-glycosylation mentioning
confidence: 99%
“…These include cardiovascular disease, inflammatory conditions, and neurodegenerative disease such as Alzheimer's disease [3], diabetes [4] and cancer [5]. Furthermore, interest in employing anti-oxidants from natural sources to increase shelf life of foods is considerably enhanced by consumer preference for natural ingredients and concerns about the toxic effects of synthetic anti-oxidants [6].…”
Section: Introductionmentioning
confidence: 99%
“…9) It has been found that high glucose induces ROS and then upregulates TGF-1 and extracellular matrix (ECM) expression in glomerular mesangial cells. 10) Evidence has also shown that antioxidants can effectively inhibit high glucose induced TGF-1 and fibronectin upregulation.…”
mentioning
confidence: 99%